Carbon nitride-based nanocaptor: An intelligent nanosystem with metal ions chelating eﬀect for enhanced magnetic targeting phototherapy of Alzheimer's disease. (January 2021) - Gong, Ling; Zhang, Xing; Ge, Kezhen; Yin, Yiming; Machuki, Jeremiah Ong'achwa; Yang, Yun; Shi, Hengliang; Geng, Deqin; Gao, Fenglei
Abstract: Metal ions imbalance, a well-established pathologic feature of alzheimer's disease (AD), ultimately results in the deposition of amyloid-β peptide (Aβ) proteins and Aβ-induced neurotoxicity. Herein, to overcome these hurdles, an intelligent Aβ nanocaptor with the capacity to chelate metal ions and targeted therapy is developed by anchoring carbon nitride (C3 N4 ) nanodots to Fe3 O4 @mesoporous silica nanospheres, and decorated with benzothiazole aniline (BTA) (designated as B–FeCN). The C3 N4 nanodots could effectively capture superfluous Cu 2+ to suppress the formation of Cu 2+ -Aβ complex thereby eliminating Aβ aggregation. Simultaneously, the nanocaptor enables local low-temperature hyperthermia to promote the dissolution of preformed fiber precipitates, therefore, maximizing the therapeutic benefits. Owing to its favorable photothermal effect, the blood-brain barrier (BBB) permeability of the nanocaptor is noticeably ameliorated upon laser illumination, which conquers the limitations associated with traditional anti-AD drugs, as evidenced by in vivo and in vitro studies. Besides, leveraging on the magnetic properties of Fe3 O4 core, the nanocaptor is magnetized to access to the targeted Aβ regions under extrinsic magnetic field. BTA conjugation, which specifically binds to the β2 position of the Aβ fibers, executes specific targeting at Aβ plaques, and synchronously endows the BTA-modified nanocaptor with fluorescent imaging property for sensitively detecting Aβ aggregates. In view of these superiorities, nanocaptors combine metallostasis restoration and Aβ targeted therapy can surmount the interference of copper ions, enhance BBB permeability and protect cells against Aβ-induced neurotoxicity, which provides new avenues for developing neuroprotective nanosystems for the treatment of alzheimer's disease.